The Impact of Corporate Social Responsibility and Corporate Governance on Firm Performance: A Study of ESG Quality 45 IDX-KEHATI - Cuandra, Fendy; Lie, Hardy Winata (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The KEHATI-listed companies have displayed commendable SRI performance across financial metrics and transactional liquidity. Among these firms, PT Danone Indonesia faced a Corporate Social Responsibility (CSR) issue in 2012 due to the uneven distribution of benefits, which prompted community protests and undermined the company's efficacy, ultimately impacting its performance. The overarching objective of this study is to explore and comprehend the relationship between CSR, corporate governance, and their potential impact on the performance of ESG QUALITY 45 IDX KEHATI listed on the Indonesia Stock Exchange (IDX). The study utilized panel regression analysis to analyze data collected over five years (2017-2021) from IDX. The research implies that there is no substantial relationship between corporate governance and performance. However, the findings evidence implies that there is a strong negative relationship between CSR and ROE, while ROA remains unaffected. In terms of control variables, the study found no significant correlation between firm size and ROA and ROE, while leverage had shown a substantial negative influence on both financial performance measures. This research sheds light on the connection between CSR, corporate governance, and business performance.